CHROMOSOMAL ABNORMALITIES IN EARLY PREGNANCY LOSSES: A STUDY OF 900 SAMPLES - Bozhinovski, Gj; Terzikj M; Kubelka-Sabit K; Jasar Dz; Lazarevski S; Livrinova V; Plasheska Karanfilska D (Sciendo, 2024)
Chromosomal abnormalities are the most common causes of early pregnancy losses (EPLs). In this study, we aimed to evaluate the incidence and spectrum of chromosomal abnormalities in EPLs and correlate them with different clinical characteristics. We performed Quantitative Fluorescent PCR (QF-PCR), followed by subtelomeric Multiplex Ligation Probe Amplification (MLPA) analysis to detect chromosomal abnormalities in 900 products of conceptions (POCs) from EPLs collected over a period of 10 years. Chromosomal abnormalities were present in 56.25% of uncontaminated EPLs, with significantly higher incidence in women ≥36 years (71.37%, p<0.0001) in comparison to women ≤30 years of age (43.40%). Trisomies were also more common in women ≥36 years (79.68%, p<0.0001) than in those ≤30 years of age (48.70%). In contrast, triploidy and monosomies were more prevalent in women ≤30 years of age (26.09%, p<0.0001 and 16.52%, p=0.0066 respectively) than in women ≥36 years of age (6.42% and 6.42% respectively). Trisomy 16 was more common in women ≤30 (39.29%, p=0.0009) than in those ≥36 years of age (16.78%), while trisomy 22 was predominant among women ≥36 (23.49%, p=0.013), and was not present in the group of women ≤30 years of age. The frequency of chromosomal abnormalities in POCs from women with sporadic (61.19%) was higher than in those with recurrent EPLs (55.21%). This difference, however, was not statistically significant (p=0.164). Although some differences in the chromosomal aneuploidy rates among women with different ABO blood groups, as well as among 6-8 and 9-11 gestational week EPLs were observed, further larger studies are required to confirm these findings. In conclusion, our study enriches the knowledge about chromosomal abnormalities as a cause of EPLs and confirms the higher incidence of foetal chromosomal abnormalities in EPLs in women of older reproductive age. Furthermore, it shows that using QF-PCR and MLPA methodologies, a high detection rate of chromosomal abnormalities in EPLs can be reached.
Keywords: Chromosomal abnormality; MLPA; QF-PCR; early pregnancy loss (EPL)